Mazamas, Patos criollos y anguilas de lodo: Restos de subsistencia del asentamiento precolombino “Loma Salvatierra”, Llanos de Mojos, Bolivia. - von den Driesch, Angela; Hutterer, Rainer (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
We present results of the analysis of an assemblage of faunal remains from trench 4 of the pre-Colombian site “Loma Salvatierra”, situated close to the actual village Casarabe in the Llanos de Mojos, Bolivia. According to radiocarbon dates this site was occupied between 600 and 1400 A. D. The bone and shell samples document a high diversity of species belonging to five vertebrate classes as well as to molluscs, as shown in tables 1–7. Numerous species associated with water reflect the aquatic environment which surrounded the settlement, in which deer species, particularly of genus Mazama, represented the most important source of meat. Absence of deer and decline of fish in the faunal assemblage of the younger levels points to a drier climate during the ultimate phase of the settlement at the summit of the mound. Frequently observed osteo-pathological modifications of the foot bones of Muscovy ducks (Cairina moschata) suggest a beginning of domestication of these birds in Bolivia. The article will be available as a PDF in the near future.